1971
DOI: 10.1351/pac197126020209
|View full text |Cite
|
Sign up to set email alerts
|

Dilute solution properties and molecular characterization of polyvinyl chloride

Abstract: Dilute solution properties of twenty-five PVC fractions prepared from commercial and experimental bulk-polymerized PVC samples have been investigated by means of light-scattering, viscometry and exclusion-chromatography The following Mark-Houwink-Sakadura relationships: []2YC = 1,63 10-2 M°76° x 1.017 c.gs. I 125t -2 ir2 At 0.725 >< 1 02 Lflicyclohexanone -: ' c.g.s.have been found to be valid in a range of Mw-values between 6400 and 650000.The validity of various extrapolation procedures, proposed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Cyclohexanone is most often used for viscosity measurements on PVC polymer 50,51 . However, THF, has been the most appropriate solvent, 52,53 as it avoids the presence of aggregates (non‐soluble portion of PVC). The solubility parameter, δ, of PVC is about 19.4 MPa 1/2 , and is therefore resistant to non‐polar solvents that have a lower solubility parameter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclohexanone is most often used for viscosity measurements on PVC polymer 50,51 . However, THF, has been the most appropriate solvent, 52,53 as it avoids the presence of aggregates (non‐soluble portion of PVC). The solubility parameter, δ, of PVC is about 19.4 MPa 1/2 , and is therefore resistant to non‐polar solvents that have a lower solubility parameter.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not an absolute experiment, since viscosity depends on a series of other molar properties besides mass, viscosimetric experiments show the existence of a relationship between molecular size and viscosity of macromolecular solutions. In a plot of inherent viscosity, η inh , or reduced viscosity, η red , against solution concentration, extrapolating to a concentration equals to zero, the intrinsic viscosity, [ η ], is obtained, which is further used to calculate the viscosimetric‐average molar mass, M¯v, with the Mark‐Houwink‐Sakurada equation: []η=KMfalse¯va where [ η ] is the intrinsic viscosity or limiting viscosity number, and K and a are constants that depends of the polymer‐solvent system and temperature of the measurement 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Vries (1) showed that tetrahydrofuran (THF) solution of PVC fractions in the molecular weight range 6400 -650 000 g/mole obeyed the following Mark-Houwink relation :…”
Section: Structure Of the Pvc Chain Long Branchesmentioning
confidence: 99%
“…The degree of tacticity of samples prepared between 25 and 60°C varies only slightly and is close to 0 .53 (3, 4 ) . The branching structure of PVC can be described as consisting of very few, if any, long branches (5,6), and a few short branches-probably less than 10 short branches per 1000 repetition units. For this molecular structure, one would certainly expect that the melt flow behavior would be describable by theories for the melt flow of linear molecules.…”
Section: Introductionmentioning
confidence: 99%